IL-17 production by NKG2D-expressing CD56+ T cells in type 2 diabetes. (February 2019) - Phoksawat, Wisitsak; Jumnainsong, Amonrat; Leelayuwat, Naruemon; Leelayuwat, Chanvit
Highlights: High level IL-17 production of T cells expressing CD56 associated with NKG2D was identified in T2D patients. IL-17 produced by CD56+ T cells with NKG2D+ population of T2D patients was positively correlated with HbA1c level. NKG2D Hi CD56+ T cells may be potentially involved in the pathogenesis and severity of T2D. NKG2D stimulation may associate with the signaling pathway(s) of IL-17 production in CD56+ T cells. Abstract: T cells expressing CD56 (identified as CD3+CD56+) play a potential role in activation or regulation of other immune cells by secreting various cytokines. We hypothesized that these cells expressing the natural group 2, member D (NKG2D) could produce high levels of interleukin (IL)-17 in type 2 diabetes (T2D). CD56 + T cells expressing NKG2D of T2D patients, particularly in poor glycemic control (PC) predominantly produced higher IL-17 compared to the NKG2D negative population. IL-17 production of CD56 + T cells with NKG2D + was positively correlated with the level of HbA1c (N = 22, R 2  = 0.120 and P  =  0.044). Interestingly, CD56+ T cells with NKG2D Hi of T2D patients had significantly higher IL-17 production than those of CD56 + T cells with NKG2D Low ( P  =  0.027) and showed statistically significant with P -value < 0.001 compared to CD56 + T cells with NKG2D Hi of non-diabetic individuals (ND). In summary, CD56 + T cells expressing NKG2D, especially in the NKG2D Hi population may be involved in pathogenesis and severity of T2D via IL-17.